Social Comparison on Facebook, Rumination, and Coping Styles Among Young Adults with Symptoms of Depression during Covid-19 Pandemic - Charry M. Sison (Future Science / FSH-PH Publications, 2026)
This study examined the relationships among social comparison on Facebook, rumination, coping styles, and depressive symptoms among university students, with the aim of informing a targeted campus-based intervention. Using a descriptive-correlational design, data were collected from 336 respondents and analyzed through descriptive statistics, group difference testing, and Pearson correlation. Results revealed that a substantial proportion of students experienced moderate to severe depressive symptoms. Social comparison was positively and significantly associated with rumination, while rumination demonstrated significant relationships with problem-focused, emotion-focused, and avoidant coping styles. Level of depression emerged as a significant factor influencing social comparison, rumination, and coping patterns, suggesting that psychological condition plays a stronger role than demographic characteristics in shaping cognitive and behavioral responses. The findings indicate that repetitive negative thinking serves as a central mechanism linking social comparison and emotional distress. Grounded in these results, an innovative intervention framework titled CAMPUS CAREquest was developed to address the cognitive, behavioral, and environmental factors identified in the study. The program integrates mindfulness-based cognitive awareness, digital comparison moderation, resilience-focused coping enhancement, and stigma-reduction strategies to promote a supportive campus climate. By targeting rumination and maladaptive comparison while strengthening adaptive coping and peer support systems, the intervention seeks to reduce depressive symptoms and foster long-term psychological resilience. The study contributes to the growing body of literature on social media use and student mental health and offers a data-driven, contextually grounded model for institutional mental health promotion in higher education settings.